Development of the information technology for checking textual procedures for logical coherence and completeness - Hutsa, Oleh; Igumentseva, Nataliya; Dovgopol, Nina; Yakubovska, Sofiia (Eastern-European Journal of Enterprise Technologies, 2017)
Analysis of existing approaches to the development of schedules (procedures) in a textual form containing description of branching processes was made. It was established that visualization with the help of the system analysis methods (in particular, BPMN notation) is the most effective tool for developing branching processes. It was also established that the absence of clear rules for development of schedules (procedures) in a textual form causes a fairly large number of errors in descriptions of the branching processes worked out by the specialists having no sufficient skills in using algorithmizing (of the forty checked process descriptions, errors were found in 75 % schemes converted from texts). The IT was developed for checking textual procedures containing descriptions of branching processes. It is based on visualization using BPMN notation which allows one to find errors of logical coherence and completeness. Effectiveness of the proposed IT was demonstrated on the example of checking a law text with a description of a branching process. The developed IT is quite simple in its mastering for the specialists possessing a certain level of skills in algorithmization and can be applied in any sphere of activity describing processes in a textual form.